THE EFFECT OF STOP AND DARE STRATEGY ON THE STUDENTS’ ABILITY IN WRITING SKILL AT THE ELEVENTH GRADE OF SMK SWASTA KRISTEN TOMOSA 1 GUNUNGSITOLI IDANOI IN 2022/2023 - Ester Gea, Wildem Grant; Zebua, Elwin Piarawan; Zega, Riswan; Harefa, Afore Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
There were some problems that students writing hortatory exposition text first students were difficult to find any ideas in writing hortatory exposition text, second did not know how to organize paragraph, third students did not able to write hortatory exposition text with correct structure. The purpose of the research was to find out the significant effect of Stop and Dare Strategy on the Students’ Ability in Writing Skill at the Eleventh Grade of SMK Swasta Kristen Tomosa 1Gunungsitoli Idanoi in 2022/2023. The researcher used quantitative research with quasi experimental design, by pretest and posttest to the experimental group and control group. The sample of the research were consisted of 60 students. The researcher concluded there was a significant effect of Stop and Dare Strategy on the Students’ Ability in Writing Skill at the Eleventh Grade of SMK Swasta Kristen Tomosa 1 in 2022/2023 at the significant level 5%.